2001
DOI: 10.1094/cchem.2001.78.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid Oxidation on Dough Bleaching

Abstract: The effect of lipid composition and oxidation on dough bleaching has been determined. At >2.25% (flour basis), pure linoleic acid was very efficient in degrading β‐carotene in dough, unlike colza, corn, peanut, soy, or sunflower oil, which were mainly characterized by different polyunsaturated fatty acids content. In a very oxidized state, as determined by a peroxide index of >15 meq/kg of oil, sunflower oil (rich in polyunsaturated fatty acids) had a major bleaching activity on β‐carotene when compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…According to the inventors, other advantages are (i) no excess formation of FAs (with regard to off‐flavors and/or yeast activity), (ii) a dough bleaching effect, and (iii) no hydrolysis of shortening, oil, or milk fat added to the dough. A dough bleaching effect, as measured by beta ‐carotene degradation, was also observed earlier by Mercier and Gélinas () when adding a lipase (AY30 from Amano Enzyme [Ill., U.S.A.]) together with sunflower oil and linoleic acid.…”
supporting
confidence: 78%
“…According to the inventors, other advantages are (i) no excess formation of FAs (with regard to off‐flavors and/or yeast activity), (ii) a dough bleaching effect, and (iii) no hydrolysis of shortening, oil, or milk fat added to the dough. A dough bleaching effect, as measured by beta ‐carotene degradation, was also observed earlier by Mercier and Gélinas () when adding a lipase (AY30 from Amano Enzyme [Ill., U.S.A.]) together with sunflower oil and linoleic acid.…”
supporting
confidence: 78%
“…In the field of food science, salt is generally considered to be an important chemical compound (additive), since it not only affects palatability or taste, but also affects the structural and physical properties of food. There is a long history of excellent studies documenting the various properties of salt (Cardoso et al, 2008;Mercier and Gelinas, 2001;Gou et al, 2003;Ishikawa et al, 2006;Kuda et al, 2007;Murphy et al, 1998;Rowe et al, 2009;Shigematsu et al, 2007;Sofos, 1983;Steel and Torrie, 1980;Kaewmanee et al, 2011;Toyosaki et al, 2006;Ukai et al, 2008;Vardhanabhuti and Foegeding, 2008;Wang et al, 2011). In our study, a number of interesting findings have suggested that the presence of salt in the fermentation process accelerates dough fermentation.…”
Section: Introductionmentioning
confidence: 53%
“…Aerobic mixing of flour and water results in the loss of free fatty acids within 10 min, but not the loss of other nonphosphorus lipids. Losses of free fatty acids can occur through lipoxidase oxidation of essential fatty acids and concomitant enzymatic oxidation of free fatty acids (Mercier & Gélinas, 2001).…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%